Implementation of the Blended Learning Model to Increase Students' Motivation to Learn Mathematics - Fauziah Pasaribu; Wiwik Novitasari; Fitriani Fitriani (CV. Media Inti Teknologi, 2022)
The problem of this research is the low motivation of students to learn mathematics, the ability of teachers to manage learning, student learning activities are low. To overcome this problem, a Blended Learning learning strategy was applied. The purpose of this study was to increase students' motivation to learn mathematics, improve teacher performance in managing learning and improve student learning activities by implementing the Blended Learning learning model at SMA N 6 Padangsidimpuan. This type of research is classroom action research (CAR). The subjects in this study were students of class X MIA 1 SMA N 6 Padangsidimpuan which consisted of 34 students. Data collection techniques are questionnaires and observations. Descriptive data analysis technique. The percentage of student questionnaire results in the first cycle was 50.15% to 89.97% in the second cycle and the increase in the percentage of student questionnaires was 39.82%. Student activity in learning increased, this was obtained from the percentage of 63.08% in the first cycle and 83.36% in the second cycle with an increase of 26.89%. Teacher performance activities increased with the acquisition of a percentage of 54.27% in the first cycle to 83.36% in the second cycle with an increase of 29.9%. So this research stopped in cycle II . The results of this study show that the Blended Learning learning model can increase students' learning motivation, can improve teacher performance and increase student learning activities at SMA N 6 Padangsidimpuan.